2018
DOI: 10.1038/s41467-018-06792-z
|View full text |Cite
|
Sign up to set email alerts
|

mRNAs and lncRNAs intrinsically form secondary structures with short end-to-end distances

Abstract: The 5′ and 3′ termini of RNA play important roles in many cellular processes. Using Förster resonance energy transfer (FRET), we show that mRNAs and lncRNAs have an intrinsic propensity to fold in the absence of proteins into structures in which the 5′ end and 3′ end are ≤7 nm apart irrespective of mRNA length. Computational estimates suggest that the inherent proximity of the ends is a universal property of most mRNA and lncRNA sequences. Only guanosine-depleted RNA sequences with low sequence complexity are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 68 publications
4
91
0
Order By: Relevance
“…Some observations suggest that the inherent folding of RNA may contribute to the formation of the "closed-loop" nature of mRNPs. For example, the ends of purified mRNAs folded in vitro are close (<10 nm) in solution (Fang et al 2011;Yoffe et al 2011;Clote et al 2012;Leija-Martínez et al 2014;Lai et al 2018). This distance is significantly smaller than the overall size of the mRNA when compacted.…”
Section: Nontranslating Mrnas Form Compacted Structuresmentioning
confidence: 99%
“…Some observations suggest that the inherent folding of RNA may contribute to the formation of the "closed-loop" nature of mRNPs. For example, the ends of purified mRNAs folded in vitro are close (<10 nm) in solution (Fang et al 2011;Yoffe et al 2011;Clote et al 2012;Leija-Martínez et al 2014;Lai et al 2018). This distance is significantly smaller than the overall size of the mRNA when compacted.…”
Section: Nontranslating Mrnas Form Compacted Structuresmentioning
confidence: 99%
“…In particular, probing data alone cannot distinguish short-range and long-range base pairings. For long RNAs, the existence of the latter, however, has been shown experimentally [13] as well as theoretically [14,15]. Thus, even combined with experimental data, there are still numerous RNA folds consistent with the probing data.…”
Section: Introductionmentioning
confidence: 56%
“…1. As a consequence, our method is well suited to deal with the long-range base pairings, these being a prominent feature of RNA secondary structures [13,14]. The answer to each question produces a split of the ensemble into two sub-samples, and we arrive at smaller sub-samples via successively querying and answering.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, though, that the distance between stop codon and the 3' poly(A) may not directly depend on the length of the interconnecting mRNA sequence. First of all, an almost inevitable presence of secondary structure elements pulls together the ends of any sufficiently long RNA fragment [75]. Besides, it was shown that termination factor eRF3 serves as a bridge between termination/post-termination complex and PABP through specific protein-protein interactions [76].…”
Section: Discussionmentioning
confidence: 99%